Knowledge Management and Web 3.0 Next Generation Business Models - Kautish, Sandeep; Bedi, Pradeep; Bhardwaj, Aradhana Balodi; Chakkarvarthy, Divya Midhun; Chouhan, Vineet; Garg, Deepa Sahai; Garg, Seema; Goswami, Shubham; Goyal, S. B.; Gupta, Tarakeshwar; Hakeem, Oridoye Tomide; Java, Sandhya; et al. (De Gruyter Series on Smart Computing Applications,, 2022)
Knowledge Management makes the management of information and resources within a commercial organization more effective. The contributions of this book investigate the applications of Knowledge Management in the upcoming era of Semantic Web, or Web 3.0, and the opportunities for reshaping and redesigning business strategies for more effective outcomes.